Kinetic and Isotherm Studies for Nickel (II) Removal Using Novel Mesoparticle Graphene Sand Composite Synthesised From Sand and Arenga Palm Sugar - Zularisam, A. W.; Norul Wahida, Kamaruzaman (IOP Publishing, 2017)
Nickel (II) is one of the most toxic contaminants recognised as a carcinogenic and mutagenic agent which needs complete removal from wastewater before disposal. In the present study, a novel adsorbent called mesoparticle graphene sand composite (MGSCaps) was synthesised from arenga palm sugar and sand by using a green, simple, low cost and efficient methodology. Subsequently, this composite was characterised and identified using field emission scanning electron microscope (FESEM), x-ray diffraction (XRD) and elemental mapping (EM). The adsorption process was investigated and optimised under the experimental parameters such as pH, contact time and bed depth. The results showed that the interaction between nickel (II) and MGSCaps was not ion to ion interaction hence removal of Ni (II) can be applied at any pH. The results were also exhibited the higher contact time and bed depth, the higher removal percentage of nickel (II) occurred. Adsorption kinetic data were modelled using Pseudo-first-order and Pseudo-second-order equation models. The experimental results indicated pseudo-second-order kinetic equation was most suitable to describe the experimental adsorption kinetics data with maximum capacity of 40% nickel (II) removal for the first hour. The equilibrium adsorption data was fitted with Langmuir, and Freundlich isotherms equations. The data suggested that the most fitted equation model is the Freundlich with correlation R2=0.9974. Based on the obtained results, it can be stated that the adsorption method using MGSCaps is an efficient, facile and reliable method for the removal of nickel (II) from waste water.